Pola Sebaran Echinodermata Pada Ekosistem Lamun di Pulau Rhun Maluku Tengah Provinsi Maluku - Natsir, Nur A.; Allifah AF, Asyik N.; T, Rosmawati; Jamdin , Zamrin (Jurnal Biologi Papua, 2023)
Echinoderms are benthic fauna whose existence has an impact on the fertility level of the bottom substrate. Aside from being a deposit feeder which destroys most of the sediment, it also causes the process of oxygenation of the top layer of sediment. The purpose of this study was to determine the distribution pattern of echinoderms in the seagrass ecosystem from February to March 2021 on Rhun Island, Central Maluku. This research was carried out on Rhun Island, Banda Naira District. The research location was divided into three stations based on the habitat characteristics at each station. Station I (a beach of fine sand and rocks with a wide expanse of seagrass and a sandy and gravel substrate), Station II (a rocky beach, a fairly wide seagrass with a gravel and sandy substrate). Station III (fine sand beach, seagrass spreaded unevenly and not too dense with gravel and rocky substrate). The results showed that 4 classes of Echinoderms were found with 307 individuals. The physical and chemical environmental factors state that it still met the safe limits for Echinodermata life. The distribution of Echinodermata had a clustered and uniform pattern. Key words: benthic; Echinodermata; Rhun Island; seagrass.